Management control research in the banking sector A critical review and directions for future research - Gooneratne, T.N.; Hoque, Z. (Emerald Publishing, 2012)
Purpose – This paper aim to review existing research in the management control systems field in the banking industry. It identifies gaps in the existing literature and suggests some directions for future research. Design/methodology/approach – The review was carried out principally by consulting leading accounting journals, followed by other relevant journals covering all publications from the inception of the particular journal to 2010. The published articles are categorized by their research topics, theories, methodologies and settings. Findings – The review reveals a dearth of detailed studies on management controls in the banking sector. As evident from the sizeable number of descriptive studies, most prior studies do not engage in an in-depth inquiry into control issues of banks, and most lack clear articulation either theoretically or methodologically. It finds that currently little is known on the concerns encountered by banks and the nature of management control practices deployed. Research limitations/implications – This review is selective and, while illustrative of the state of management control research in the banking sector, does not attempt a comprehensive coverage of all research. However, it identifies gaps in the current literature and makes calls for further research on a number of management control issues in the banking industry. Further, in light of the review findings, the paper offers some lessons and insights for practicing managers. Originality/value – Although some general reviews on various facets of management accounting across time have been undertaken by past researchers, industry-based reviews have not been their focus. Through a systematic review of management control research in the banking arena, this paper shows that despite both the significant position occupied by the banking industry in nations’ economies and the importance of management controls for banks, there remains a need for researchers to pay adequate attention to exploring control issues in this sector.
Keywords: Control; Management control systems; Banking